High Temperature Winkler gasification of Rhenish lignite in an optimized 500 kWth pilot plant. (1st February 2023) - Heinze, Christian; May, Jan; Langner, Eric; Ströhle, Jochen; Epple, Bernd
Highlights: Pilot scale fluidized bed gasifier. Gasification of lignite and hearth furnace coke. Performance evaluation. Abstract: Gasification processes are an important part of a broad variety of value chains from low grade feedstocks to energy. The process considered in this work consists of a 0.5 MWth fluidized bed gasifier, a gas cleaning unit and a catalyst test rig. This paper presents experimental results from the stand-alone operation of the gasifier in order to investigate the behavior of the gasification of two feedstocks, a dried lignite steam coal and a commercially available low sulfur, low ash lignite. Furthermore, the results of the gasification of the gasifier start-up material hearth furnace coke are given. The reactor with a height of 11 m and an inner diameter of 400 mm was operated at up to 870 °C. Carbon dioxide, steam and oxygen can be introduced into the reactor through different nozzle levels. Four test campaigns were conducted and seven balance points with different feedstock and loads were investigated. The results show carbon conversions of almost 96 % and cold gas efficiencies up to 65 % with coal from fluidized bed drying showing the highest cold gas efficiencies and carbon conversions. Several trace gases were measured by Fourier-Transform Infrared Spectroscopy and a positive correlation between benzene and methane concentration is detected. The experience gained serves as a basis for the gasification step in the polygeneration process and for gasification of other feedstock, especially biogenic and anthropogenic residues.